Black Matrilineage, Photography, and Representation Another Way of Knowing - Deschler Canossi, Lesly; Lopez-Diago, Zoraida (Leuven University Press, 2022)
Black Matrilineage, Photography, and Representation: Another Way of Knowing' questions how the Black female body, specifically the Black maternal body, navigates interlocking structures that place a false narrative on her body and that of her maternal ancestors. This volume, which includes a curated selection of images, addresses the complicated relationship between Blackness and photography and, in particular, its gendered dimension, its relationship to health, sexuality, and digital culture - primarily in the context of racialized heteronormativity. With over forty contributors, this volume draws on scholarly inquiry ranging from academic essays, interviews, poetry, to documentary practice, and on contemporary art. 'Black Matrilineage, Photography, and Representation: Another Way of Knowing' thus offers a cross-section of analysis on the topic of Black motherhood, mothering, and the participation of photography in the process. This collection challenges racist images and discourses, both historically and in its persistence in contemporary society, while reclaiming the innate brilliance of Black women through personal narratives, political acts, connections to place, moments of pleasure, and communal celebration. It serves as a reflection of the past, a portal to the future, and contributes to recent scholarship on the complexities of Black life and Black joy.